2020
DOI: 10.1002/pen.25366
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal analysis of a couple stress fluid in blade coating process

Abstract: In this paper, a nonisothermal analysis for the process of blade coating of an incompressible couple stress fluid is presented using both plane and exponential coaters. The governing system is simplified using lubrication approximation theory (LAT). The interesting quantities from engineering point of view like normalized pressure, maximum pressure, pressure gradient, velocity, and effects of involved parameters on temperature distribution, which influence the coating process are evaluated. It is observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Consequently, it is predicted that the couple stresses may emerge in remarkable magnitudes in alike fluid flows. The non-isothermal couple stress fluid model was analyzed by Mughees et al [38] in a blade coating. It is observed that the increase in couple stress parameter boosts up the load and reduces the coating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is predicted that the couple stresses may emerge in remarkable magnitudes in alike fluid flows. The non-isothermal couple stress fluid model was analyzed by Mughees et al [38] in a blade coating. It is observed that the increase in couple stress parameter boosts up the load and reduces the coating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang 26 studied power-law fluid to analyze the blade coating process and approximate solutions were developed using a simple blade coater. Recently Mughees et al 27 studied blade coating phenomenon using a Couple stress fluid and presented its non-isothermal analysis by simplifying the governing equations by applying lubrication approximation theory. The obtained results were presented by graphs and tables to highlight important physical quantities for engineers including pressure, velocity, load, pressure gradient, and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Mughees et al 20 developed the mathematical model for non-isothermal couple stress fluid for blade coating process. They also used LAT to simplify the governing equations.…”
Section: Introductionmentioning
confidence: 99%